Kajian Politik Hukum sebagai Instrumen Menjamin Stabilitas Sistem Ketatanegaraan Indonesia - Habibul Umam Taqiuddin; Titi Tantri (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
This research aims to: (1) analyze the role of legal politics in maintaining the stability of the state system, and (2) assess the conformity of legal political policies with legal principles and constitutional principles. The research uses normative legal methods with a statutory and conceptual approach. The legal materials include primary, secondary, and tertiary materials analyzed through grammatical, systematic, and teleological interpretations, supported by a study of legal theory and legal principles. The results of the research indicate, first, that legal politics functions as a strategic instrument in maintaining the stability of state administration, regulating inter-institutional coordination, and ensuring administrative order. Clearly and consistently formulated policies enable the state to balance public interests with the goals of effective governance. Second, the conformity of legal political policies with legal and constitutional principles such as legal certainty, justice, expediency, and proportionality is crucial to their effectiveness. Policies must align with higher norms, be consistent across institutions, and be easily understood and implemented. With this alignment, legal politics is not only normatively legitimate but also supports the order, stability, and sustainability of the Indonesian state system